Estudo da fermentação alcoólica de extrato da casca de abacaxi e recuperação de etanol por pervaporação com membrana de matriz mista - Sabrina de Matos Nonato (2024)
Ethanol is one of the main alternatives for replacing gasoline in the transport sector. This biofuel can be produced from various raw materials, such as agro-industrial waste, resulting from fruit processing in the food industry. In this work, the use of pineapple waste in ethanol production was evaluated. For this, direct fermentation of peel extract was carried out and a PDMS mixed matrix membrane was prepared by adding biochar, obtained through pyrolysis of stalk, peel and crown, to recover ethanol by pervaporation. Performance of the mixed matrix membrane for separation of ethanol from a synthetic water/ethanol solution (5% w/w) and fermentative musts was studied for the first time. An average yield of 88% was obtained for the fermentation of pineapple peel extract at room temperature. The 0% biochar membrane presented permeate flux of 110 g.m-2h-1 and 120 g.m-2h-1 while the mixed matrix membrane with 2% of biochar loading presented permeate flux of 40 g.m-2h-1 and 9 g.m-2h-1 for the pervaporation of commercial sucrose fermentation wort and pineapple peel extract must, respectively. The separation factor for ethanol over water and the enrichment factor were 0.07 and 1.066 for both membranes. The results showed that there are opportunities to use pineapple waste in the biofuels industry using relatively simple processes.